Strategi Komunikasi Pengembangan Pariwisata di Kelurahan Matakando Kota Bima - Irham Irham; Tasrif Tasrif (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
The implementation of tourism development policies in the Matakando Village Kota Bima requires an appropriate communication strategy. Mapping a communication strategy is one way for the government to develop regional potential in 10 Matakando Villages with all forms of available Natural Resources. Researchers examine tourism development through the implementation of communication strategies in understanding existing regulations as well as describing the use of government communication strategies to collaborate with various parties in tourism development in local areas. This situation requires a relevant collaborative approach and analysis of the suitability of the concept of implementing a communication strategy originating from regulations, observational data, collection of complementary documents to meet the needs of research on tourism development. Examined from this context, the researchers used a type of qualitative research through a literature review approach. This position places researchers to sort, select, analyze phenomena that occur within the scope of implementing communication strategy policies through a number of supporting documents, articles, tourism narratives in interpreting various issues regarding tourism development communication strategies. Based on the results of observations in the field and the results of document analysis, it was found that a number of implementations of policy communication strategies were found in the communication strategy for tourism development in Matakando Village, including adaptation to facility development and implementation of strategic policies. Facility development adaptation is related to environmental management through various supporting facilities in the development of local area spatial planning. Facility development adaptation is related to environmental management through various supporting facilities in the development of local area spatial planning. Meanwhile, the implementation of strategic policies is related to government collaboration with various parties in assisting tourism development in the Matakando sub-district.